Character Educational Values in Paddington Movie - Ridhani, Muhammad Rizqan; Emma Rosana Febriyanti; nayati Fitriyah Asrimawati (Institut Agama Islam Negeri Palopo, 2024)
Character educational values represent initiatives implemented by schools and governments to improve the moral and behavioral aspects of students, with the goal of fostering positive impacts on both individuals and their surroundings. In this study the researcher aimed to analyze a movie Paddington (2014) to identify the types of character educational values in it so that the movie can be integrated into lessons at school. This study is using a Descriptive Qualitative Method. From this research the researcher found 13 out of 18 types of Educational Values namely: social care, curiosity, hard work, honesty, discipline, appreciate achievement, friendly/communicative, responsibility, tolerance, creative, independent, democratic, and love peace. â€œPaddingtonâ€ portrays a wide range of Character Educational Values that are skillfully woven into its storyline and characters, making this movie an excellent tool to be used for learning character educational values.